Emergence and Evolvement of Buyer Seller Relationships in Supply Chain - Khandelwal, Srishti (2013)
It is now widely recognized that supply chains, not individual organisations, are responsible for the success or failure of businesses. The current trend in the supply chain is that of collaborative relationships. The perception is that the competitive advantage lies with the partners of a supply chain rather than the company itself. A lot of academic research has been done on the functioning of buyer seller relationships. But the genesis of these relationships still remains vague. This research focuses on the emergence and evolvement of buyer supplier relationships in India. For the purpose of this study, a case study analysis has been done with an SME that is a secondary steel manufacturer in India. The findings of this research demonstrate that relationships with first tier partners are maintained but not to a very great extent. Selection of these partners is not done on a very scientific basis but is done keeping individual interest in mind. The main factors that lead to growth or termination of a relationship are identified to be cost and trust. Networking in a supply chain is found to be very crucial as well especially for SME’s as moving to better networks gives the firm better reputation. The functioning of supply chain relationships in a developing country is found to be very different from their developed counterparts with no focus on technology. The supply chain visibility was also found to be poor, as business strategies were not aligned with supply chain strategies. An analysis on the Indian steel industry helps understand the scenario better. Further empirical investigations will help strengthen the validity of these findings.